Neuroscience of self and self-regulation. [article]. - Heatherton, Todd F.
As social species, humans have a fundamental need to belong that encourages behaviors consistent with being a good group member. Being a good group member requires the capacity for self-regulation, which allows people to alter or inhibit behaviors that would place them at risk for group exclusion. Self-regulation requires four psychological components. First, people need to be aware of their behavior so as to gauge it against societal norms. Second, people need to understand how others are reacting to their behavior so as to predict how others will respond to them. This necessitates a third mechanism, which detects threat, especially in complex social situations. Finally, there needs to be a mechanism for resolving discrepancies between self-knowledge and social expectations or norms, thereby motivating behavior to resolve any conflict that exists. This article reviews recent social neuroscience research on the psychological components that support the human capacity for self-regulation.-(from the author)